Boosting Circular Economics On Municipal Waste Management: Case Study In, West Java - Chaerudin, Iman; Vita sarasi, Vita sarasi (Al-Makki Publisher, 2023)
The economic development and population rapid growth has led to the uncontrolled increase of Municipal Solid Waste (MSW) generations in West Java since around half of the world’s waste production is MSW from the residential, commercial, and service sectors. Currently, the government implements some actions of MSW management, such as composting programs, recycling programs, and MSW banks. Although the programs run well they can only reduce 18% of MSW every day. Thus, the government is still facing MSW problems while landfill, as the most common waste disposal practice, is considered unsustainable. Now the government is trying to shift its mind that sound waste management should generate economic, social & environmental value while offering great opportunities to the private sector for revenue-making business instead of a cost center. The purpose of this study is to develop a circulating economic business model on the recycling and recovery system of MSW using green technology to create alternative sustainable products for social development business as a circulating economy. This is applied research that uses the qualitative analysis method to get a zero household waste management model based on secondary data (from the period of 2019-2022) from the pilot project at the Nambo site, Cirebon plant, and Cibiru site. The result of the study is beneficial for the government in supporting its policies to recycle & recover MSW. Moreover, the integrated business process of MSW will encourage the private sector to invest in sustainable waste management businesses.